Quo Vadis the Importance of Ratification of the Rome Statute for Law Enforcement and Human Rights in Indonesia in Terms of Legal System Theory - Yogi Syahputra Alidrus (PT Publikasiku Academic Solution, 2023)
This study aims to provide an understanding of the urgency of the importance of Ratifying the Status of Rome for the enforcement of law and human rights in Indonesia which uses an analytical knife from Lawrence M Friedman's legal system theory. In Law number 26 of 2000 concerning the Human Rights Court has full legality in dealing with crimes of genocide and crimes against humanity but is this enough to make law enforcement in Indonesia fight or resolve human rights cases such as the Peter case, Semanggi I case and the -other cases need to apply a grand design for the settlement of these cases even more than that Indonesia's ratification will place Indonesia as one of the main supporters of international justice. In its implementation, Indonesia will join more than half of the world's people in ensuring that an effective justice system will prevent the worst crimes ever committed against humanity and ensure protection for all nations in the world, including Indonesia itself. This research is normative by using scientific literature such as written rules, theoretical and legal dogmas so that problems are resolved regarding the urgency of the importance of implementing the Rome Statute in Indonesia fulfilling three discussions, namely 1) The Importance of Ratification of the Rome Statute for Law Enforcement in Indonesia, 2) The Importance of Ratification of the Rome Statute Can Prevent Impunity in a Country, 3) Legal System Theory as a model in the application of Rome Statute ratification in Indonesia. so that this study can know the importance of the Rome Statute rules in Indonesia because they can be bound by international courts.